Modified Technology Acceptance Model For Measuring Online Training Adoption in Indonesia - Mohammad Rizal Gaffar; Tangguh Dwi Pramono; Nugroho Hardiyanto (Profesional Muda Cendekia Publishing, 2022)
The pandemic has changed almost all of the ways people do their activities. One of the changes felt was a change in learning activities that were forced to be held online. For approximately 2 years the implementation of knowledge transfer is carried out remotely using certain applications with the support of existing technology and the internet. Transformed learning is not only formal learning in schools but also informal learning such as online courses or training. The pandemic has indirectly catalyzed the growth of 2 new business sectors, namely the health sector and the education sector / Education Technology. Indonesia is a country with a very large population and is very attractive to foreign business players, including those in the Education Technology sector. Therefore, research to analyze the adoption of online training is important to help local startups in the Education Technology sector develop products that are suitable for the Indonesian market. This study aims to examine the factors that influence the behavior of online course/training adoption. The proposed model is a development of the TAM model which is given several additional variables. This research used a set of questionnaire and valid data gathered from 161 samples. Data were analyzed by using Partial Least Square. The result shows that the model has a strong predictive power for measuring future use behavior.